2020
DOI: 10.4094/chnr.2020.26.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the Status of the Umbilical Cord and Neonatal Health Status

Abstract: Purpose: This study aimed to identify correlations between the status of the umbilical cord and neonatal health status.Methods: In total, 172 newborns were enrolled who were admitted to the newborn nursery with a gestational age of 35 weeks or older and a body weight of 2 kg or above. Data were collected on the basic personal information of the newborns, the diameter and soft tissue status of the umbilical cord, and neonatal health status after birth. Analyses were performed using t-test, analysis of variance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(24 reference statements)
1
0
1
Order By: Relevance
“…Difference in diameter of umbilical cord between male and female neonates was not found significant in this study. This is in contrast with previous studies which all reported thick umbilical cord in males (17,(19)(20)(21)(22).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Difference in diameter of umbilical cord between male and female neonates was not found significant in this study. This is in contrast with previous studies which all reported thick umbilical cord in males (17,(19)(20)(21)(22).…”
Section: Discussioncontrasting
confidence: 99%
“…A wide diameter of cord indicates a good health of newborn. Udoh et al, Lee et al and Tahmasebi et al also reported similar results in their study (15)(16)(17). The only limitations of these studies were ultrasound guided measurement of cord thickness.…”
Section: Discussionsupporting
confidence: 61%